A mechatronic approach to a virtual laboratory service on internet. (8th March 2010) - Cheng, Marvin H-M.; Chiu, George T-C.
In engineering education, concepts taught through lectures are often complemented by practical laboratory experimentation. Students can observe dynamic phenomena that are often difficult to explain by written material in laboratory environment. To offer the hands-on laboratory experience for distant users, virtual environment is necessary. In this paper, we reported and demonstrated an innovative remotely accessible virtual laboratory. Our approach is based on the newly developed software packages. Remote control, network reliability, and safety features are integrated into the experimental hardware and software design. Distance users are able to develop and run controllers on the experiments in the virtual laboratory, and can effectively use the laboratory from anywhere over internet.